A liderança feminina como fator de sustentabilidade: um estudo com empresas do índice ICO2 da B3 - Souza, Adria Emily Ribeiro de (Brasil, 2024)
Female leadership has been recognized as an essential tool for promoting corporate sustainability. This study analyzed the relationship between the presence of women in leadership positions and sustainability in 72 companies on the ICO2 index of the Brazilian Stock Exchange (B3), using the Gretl software to identify the correlation between these variables, measured by the Gases indicator Greenhouse Effect (GHG). The results indicate that the participation of women in strategic positions has a significant role in reducing GHG emissions, and it is observed that a minimum representation of 7% of women in leadership can result in a significant reduction in gas emissions. These findings suggest that gender diversity in leadership positions can strengthen more sustainable and environmentally responsible business practices. However, the study was limited to companies listed on B3, and it is recommended that future research include organizations from other sectors and regions to expand understanding of the impact of female leadership on business sustainability.